Management of patients with peripheral arterial disease in primary care: a cross-sectional study in Germany - Kröger, Knut; Schwertfeger, M.; Pittrow, D.; Diehm, Curt (The international journal of clinical practice, 2010)
Background: Studies in the primary care setting are of high interest for assessing the management situation of patients with manifestations of atherothrombosis. Aims: Therefore, we documented diagnostic procedures, characteristics, and management of patients with symptomatic and asymptomatic peripheral arterial disease (PAD). Materials & Methods: Prospective cross-sectional study in primary care practices throughout Germany. Results: A total of 671 patients with newly diagnosed PAD were included (mean age 69.1 years; 62.1% men). Cardiovascular risk factors were highly prevalent in the total PAD group: arterial hypertension in 84.2%, hyperlipidaemia in 75.5%, present smoking in 45.0% and diabetes mellitus in 47.3%. Atherothrombotic comorbidities were also frequent: coronary artery disease in 44.9% and cerebrovascular disease in 28.1%. For confirmation of diagnosis, patients were referred to specialists in 66.9% of cases. Overall, ankle brachial index was measured in 89.0%, and a clinical PAD score assessed in 66.6% (agreement of both measures with Cohen’s kappa only, κ = 0.039; p = 0.209). Drug treatment of risk factors (as secondary prophylaxis) in line with current guidelines was reported in a high percentage of patients: 88.6% with any antiplatelet drug, 69.3% with statins, 62.4% with angiotensin converting enzyme inhibitors, 23.5% with AT1 receptor blockers and 43.9% with beta-blockers. Between asymptomatic and symptomatic PAD, differences in the risk factor/comorbidity profiles were small; however, the latter group received intensified treatment. Conclusion: Our findings confirm that patients with PAD pose a substantial challenge to physicians because of their high number of comorbidities. Compared with previous studies, management of such patients appears to have improved.
Gesehen am 06.03.2023